2014
DOI: 10.1084/jem.20140039
|View full text |Cite
|
Sign up to set email alerts
|

Exhaustion of bacteria-specific CD4 T cells and microbial translocation in common variable immunodeficiency disorders

Abstract: Common variable immunodeficiency (CVID) is characterized by abnormally low levels of antibodies in the blood and dysfunctional immune cells called CD4+ T cells. Perreau et al. now show evidence that bacteria-fighting CD4+ T cells in these patients are in a state of exhaustion due to a constant leakage of normal gut bacteria into the bloodstream, possibly due to insufficient antibody levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
91
2
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(106 citation statements)
references
References 54 publications
10
91
2
3
Order By: Relevance
“…We have recently reported that similar perturbations in gd T cells also occur in CVID (32), and in the current study we observed a trend toward an association between the levels of sCD14, an indirect marker of microbial translocation, and MAIT cell loss in CVID. Two studies have reported elevated levels of LPS in CVID (30,31) and elevated LPS levels were associated with CD4 + T cell exhaustion. This suggests that microbial translocation may underlie several perturbations in CVID and possibly explain some of the similarities in T cell anomalies between CVID and HIV infection (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently reported that similar perturbations in gd T cells also occur in CVID (32), and in the current study we observed a trend toward an association between the levels of sCD14, an indirect marker of microbial translocation, and MAIT cell loss in CVID. Two studies have reported elevated levels of LPS in CVID (30,31) and elevated LPS levels were associated with CD4 + T cell exhaustion. This suggests that microbial translocation may underlie several perturbations in CVID and possibly explain some of the similarities in T cell anomalies between CVID and HIV infection (11).…”
Section: Discussionmentioning
confidence: 99%
“…In HIV type 1 and human T cell leukemia virus type 1 infections, MAIT cells are reduced in number and display impaired functionality in response to bacterial stimulation (27)(28)(29). Microbial translocation is now recognized to have a major role in HIV immuno-pathogenesis, and recent evidence suggests that microbial translocation could be responsible for CD4 + T cell exhaustion in CVID patients (30). Elevated levels of LPS in CVID are also associated with dysbiosis of the gut microbiota (31).…”
Section: Introductionmentioning
confidence: 99%
“…Phenotypic and functional defects of CD4 + T cells in CVID patients have been reported during the last decade [35][36][37]. These abnormalities include increased activated CD4 + T-cell counts and decreased total, naive, and memory CD4 + T-cell counts (Table 2), along with functional impairment, such as reduced proliferative capacity and failure in cytokine production [37,38].…”
Section: Cd4 + T-cell Defects In Cvidmentioning
confidence: 99%
“…These abnormalities include increased activated CD4 + T-cell counts and decreased total, naive, and memory CD4 + T-cell counts (Table 2), along with functional impairment, such as reduced proliferative capacity and failure in cytokine production [37,38]. This reduction in CD4 + T-cell counts is associated with a decrease in thymic output, increase in T-cell turnover, and spontaneous apoptosis [12].…”
Section: Cd4 + T-cell Defects In Cvidmentioning
confidence: 99%
See 1 more Smart Citation